2020
DOI: 10.1155/2020/6159720
|View full text |Cite
|
Sign up to set email alerts
|

D-Dimer and Prothrombin Time Are the Significant Indicators of Severe COVID-19 and Poor Prognosis

Abstract: Objective. To investigate the value of coagulation indicators D-dimer (DD), prothrombin time (PT), activated partial thromboplastin time (APTT), thrombin time (TT), and fibrinogen (Fg) in predicting the severity and prognosis of COVID-19. Methods. A total of 115 patients with confirmed COVID-19, who were admitted to Tianyou Hospital of Wuhan University of Science and Technology between January 18, 2020, and March 5, 2020, were included. The dynamic changes of DD, PT, APTT, and Fg were tested, and the correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
182
4
25

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(235 citation statements)
references
References 17 publications
24
182
4
25
Order By: Relevance
“…Zhou et al [ 12 ] reported that multivariable regression showed increasing odds of in-hospital death associated with D-dimer > 1 μg/mL on admission. Liu et al [ 22 ] found that increased D-dimer levels at admission were closely related to death through multivariable logistic regression. Wu et al [ 23 ] also reported that D-dimer was associated with progression from ARDS to death in bivariate Cox regression analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al [ 12 ] reported that multivariable regression showed increasing odds of in-hospital death associated with D-dimer > 1 μg/mL on admission. Liu et al [ 22 ] found that increased D-dimer levels at admission were closely related to death through multivariable logistic regression. Wu et al [ 23 ] also reported that D-dimer was associated with progression from ARDS to death in bivariate Cox regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [ 11 ] reported that using ROC analyses, the AUC values for PT, FDP, and D-dimer at admission were 0.892, 0.81, and 0.809, respectively, for predicting in-hospital mortality in patients with COVID-19. Another study on COVID-19 also indicated that the AUCs of PT and D-dimer at admission were 0.643 and 0.742 for predicting mortality, and they increased to 0.937 and 0.851, respectively, at the composite endpoint [ 22 ]. Combined with these studies, we argue that the specific parameters of coagulation function, including PT-act at admission, can effectively predict the prognosis of patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many studies have been launched to evaluate the value of various serum markers in the prediction of COVID-19 severity. Such studies ranged from the use of simple affordable tests such as C-reactive protein (CRP) [3] Ferritin [4] , and D-Dimer [5] to more expensive biomarkers, such as Interleukin 6 and single cell sequencing.…”
Section: Hypothesismentioning
confidence: 99%
“…S. Typhi infection has been reported to activate the coagulation system, increase serum brinogen and D-dimer and prolong PT and APTT [18]. COVID-19 infection may lead to disturbances in the procoagulation, anticoagulation and brinolytic systems [30][31][32][33][34]; a high concentration of D-dimer and prolonged PT are associated with severe COVID-19 and a poor prognosis [24]. In this study, we found that RBCs were detected in the stool of 2 patients, PT was prolonged and D-dimer was elevated in all 6 patients, while APTTs and brinogen levels were normal.…”
Section: Discussionmentioning
confidence: 99%
“…S. Typhi can activate the coagulation system, and the consumption of coagulation factors could extend the prothrombin time (PT) and the activated partial thromboplastin time (APTT) [18]. D-dimer and PT are signi cant indicators of severe COVID-19 and a poor prognosis [24,25]. However, the correlation between the function of the coagulation system and S. Enteritidis infection remains unclear.…”
Section: Introductionmentioning
confidence: 99%